Subsoil Arbuscular Mycorrhizal Fungi for Sustainability and Climate-Smart Agriculture: A Solution Right Under Our Feet? - Sosa-Hernández, Moisés A.; Leifheit, Eva F.; Ingraffia, Rosolino; Rillig, Matthias C. (Frontiers in Microbiology, 2019)
With growing populations and climate change, assuring food and nutrition security is an increasingly challenging task. Climate smart and sustainable agriculture, that is, conceiving agriculture to be resistant and resilient to a changing climate while keeping it viable in the long term, is probably the best solution. The role of soil biota and particularly arbuscular mycorrhizal (AM) fungi in this new agriculture is believed to be of paramount importance. However, the large nutrient pools and the microbiota of subsoils are rarely considered in the equation. Here we explore the potential contributions of subsoil AM fungi to this agriculture and suggest future research goals that would allow us to maximize their benefits.